2022
DOI: 10.1038/s41598-022-17022-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigating calcification-related candidates in a non-symbiotic scleractinian coral, Tubastraea spp.

Abstract: In hermatypic scleractinian corals, photosynthetic fixation of CO2 and the production of CaCO3 are intimately linked due to their symbiotic relationship with dinoflagellates of the Symbiodiniaceae family. This makes it difficult to study ion transport mechanisms involved in the different pathways. In contrast, most ahermatypic scleractinian corals do not share this symbiotic relationship and thus offer an advantage when studying the ion transport mechanisms involved in the calcification process. Despite this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 132 publications
(134 reference statements)
0
4
0
Order By: Relevance
“…The bicarbonate ions are required for the formation of calcium carbonate crystals. Capasso et al [ 53 ] found that the bicarbonate transporter SLC4 regulates intracellular bicarbonate ion homeostasis to buffer excess H + generated during CaCO 3 precipitation and supply of HCO 3 − to the calcifying cells of the mantle tissues [ 53 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bicarbonate ions are required for the formation of calcium carbonate crystals. Capasso et al [ 53 ] found that the bicarbonate transporter SLC4 regulates intracellular bicarbonate ion homeostasis to buffer excess H + generated during CaCO 3 precipitation and supply of HCO 3 − to the calcifying cells of the mantle tissues [ 53 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“… a : Capasso et al [ 53 ], b : Przybyło and Langner [ 54 ], c : Sleight et al [ 55 ], and d : Louis et al [ 56 ]. …”
Section: Figurementioning
confidence: 99%
“…Various bicarbonate ion transporters have been reported for different coral species (Zoccola et al., 2015), including downregulation of a SLC4 member under low pH conditions (Yuan et al., 2018); however, the DEGs in our study matched different SLC families. Recently, the role of SLC13 and SLC23 in coral calcification were described for the non‐symbiotic coral Tubastraea (Capasso et al., 2022). The consistent downregulation of various SLC family proteins in corals subject to low pH in our study suggests an impairment of intracellular pH regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Normally, the first site of NH 4 + uptake in corals is the Symbiodiniaceae component, which assimilates 90% of the NH 4 + taken up via the glutamine synthetase/glutamine oxoglutarate aminotransferase pathway (GS/GOGAT) (Pernice et al, 2012;Roberty et al, 2020). Although the coral host can also assimilate NH 4 + via two pathways (GS/GOGAT and glutamate dehydrogenase pathway), and has ammonium transporters (Capasso et al, 2022), direct NH 4 + uptake is generally low (Pernice et al, 2012), except under certain stress conditions (Tang et al, 2020;Xiang et al, 2020). Unlike Symbiodiniaceae-bearing corals, non-symbiotic corals are generally unable to assimilate DIN (Muscatine et al, 1979) and instead excrete NH 4 + and urea into the surrounding water (Rahav et al, 1989).…”
Section: Discussionmentioning
confidence: 99%